PENGARUH UKURAN PERUSAHAAN, LEVERAGE, LIKUIDITAS DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS - Haris Haris; Dicky Arisudhana; Taqwa Putra Budi Purnomo Sidi Hiram (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This study aims to determine the effect of Firm Size, Leverage, Liquidity, and Growth Sales on Profitability in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2020–2023 period. The sample of this research is 46 companies in the food and beverage sub-sector that are listed on the Indonesia Stock Exchange for the 2020-2023 period. The result showed that Firm Size had a significance and positive effect on Profitability and Leverage had a significance and negative effect on Profitability. Meanwhile Liquidity and Growth Sales has no effect on Profitability.